IMPLEMENTATION DEBATING TECHNIQUE IN TEACHING SPEAKING (Descriptive Study of Student At Twelve Level of SMAN1 Curup ) - Nining Warnidah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
This research described the implementation of the debate technique in teaching speaking ofSMAN 1 Curup and analysis how debate technique can be applied for speaking class and itcan be a good way to make students’ speaking more better as their skill of languange masteryin English. The debating activity of this class is a kind of debate that different with australianor parlementary style where of Parlementary style the student present in each group contain 3members and when they present the debating activity there are 2 groups. The group ofAffirmative which agree to the motion given and the Negative group which dissagree to themotion. While on Australian style the each group has two members and in delivering activitythere are 4 group of its presentation. Two groups for Affirmative group and two group fornegative group.The observation have three steps the firsly,t to get data who students that has ability in speakingwell they will be the main group. The main group contain of 6-7 students of each class and theywill be an opposite group for other group of the class. It is about 5 group will present of theclass with the opposite team for the students who has ability well in speaking. Theobservervations had been done directly in the class, it need 4-6 weeks of each class. Secondly,they present their debating with the motion given with the turn and motion that given lotteryrandomly.Next, after the debating held of each class the observer give another activity by asking them topresent speaking individually, and there is good result, their speaking performance increaseto be better than of the first activity before debating